If the dolphin come to help: Education and Health without Boundaries for transversal competences. (30th September 2020) - Rubba, F; Scamardo, M S; Di Mauro, F; Egidio, R; Avati, P; Passione, A; Giulierini, P; Continisio, I G; Iervolino, A; Triassi, M
Abstract: Aims: Italy is a veritable bridge to the Mediterranean that peoples, civilizations and cultures pass through. The exchange, confrontation and interaction are key element that could lead to greater well-being of the communities. The project called: "If the dolphin come to help: Education and Health drive the orientation path for transversal competences toward reception and integration with the aim to promote the educational development and cultural growth of students and, at the same time, to provide schools with the opportunity to enhance their educational offerings. Methods: The geographical position leads our country to a particularly heavy task: to provide in a timely and appropriate way for the reception and livelihood of a very large number of people. Question assessed were." Who are the migrants and what happens when they land in Italy? Where are they detained and for how long? What are the reception services that take care of migrants? The first step was to clarify the subject starting from the difference between asylum seekers, refugee, beneficiary of humanitarian protection / applicants for international protection, illegal immigrant, going through the process of entry in Italy at one of the four hotspots. The students worked in 3 groups creating one short story. The second step it was to encourage students, through the role playing tool, to reflect on what it feels like to be a migrant and what feelings you feel in front of a migrant. The third step was to ask to the student to describe with only one word the feelings. Results: The stories were synthesized in a word cloud, through a string analysis algorithm in which the semantic fields of integration, acceptance and empathy prevailed. Immigration is perceived not as a problem but as a resource Conclusions: Educational and health projects shared with high schools may be a useful tool to promote integration, acceptance and social cohesion beyond the limits of fear. Key messages: Immigration today in our country is a very complex subject that is difficult to address in a few lines. Italy is on the route of the migratory flows of Africa and the Middle East. The project may be a trigger to create a place where everyone is equal and can access education, health and knowledge, not being denied because of the origin.